1983
DOI: 10.4315/0362-028x-46.5.420
|View full text |Cite
|
Sign up to set email alerts
|

Acetoin and Diacetyl Production by Homo- and Heterofermentative Lactic Acid Bacteria

Abstract: Eleven strains of homofermentative and heterofermentative lactic acid bacteria were screened for acetoin (A) and diacetyl (D) production from pyruvate and citrate in a peptone-yeast extract-glucose broth. The homofermenters, except Streptococcus faecalis subsp. liquefaciens, produced much more AD from pyruvate than from citrate; the opposite was true for the heterofermenters. Acetoin and diacetyl were produced from pyruvate as soon as growth was initiated. The production was exponential up to 24 h. Destruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…On the other hand, it has been shown that growth of L. lactis subsp. lactis biovar diacetylactis strains was not enhanced by citrate (15). Likewise, Palles et al (31) suggested that citrate did not affect the growth rate of Lactobacillus casei or Lactobacillus plantarum when it was cometabolized with glucose or galactose.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, it has been shown that growth of L. lactis subsp. lactis biovar diacetylactis strains was not enhanced by citrate (15). Likewise, Palles et al (31) suggested that citrate did not affect the growth rate of Lactobacillus casei or Lactobacillus plantarum when it was cometabolized with glucose or galactose.…”
Section: Discussionmentioning
confidence: 98%
“…mesenteroides subsp. cremoris (Lindsay et al, 1965;Collins & Speckman, 1974;Schmitt & Diviés, 1990), while high levels (Ͼ100 mg L Ϫ1 ) of acetaldehyde inhibit growth of these LAB (El-Gendy et al, 1983). It is thought that acetaldehyde acts as a hydrogen acceptor during heterofermentation with the formation of extra energy (ATP) which stimulates growth (Lindsay et al, 1965;Collins & Speckman, 1974).…”
Section: Effect Of Acetaldehyde On Lactic Acid Bacteria and Implicatimentioning
confidence: 99%
“…The process of diacetyl formation by lactic acid bacteria is poorly understood and therefore difficult to control during the manufacture of dairy products. Furthermore, a large variation in the activity of and product formation from citrate metabolism has been observed in different aromabacteria (Drinan et al 1976;E1-Gendy et al 1983;Oberman et al 1982). These differences in activity are evident from the different starter cultures that Correspondence to: J. Hugenholtz are used for the production of specific dairy products (Driessen and Puhan 1988;Galesloot 1962;Stadhouders 1974).…”
Section: Introductionmentioning
confidence: 99%